Diabetes Attenuates the Contribution of Endogenous Nitric Oxide but Not Nitroxyl to Endothelium Dependent Relaxation of Rat Carotid Arteries - Li, Jasmin Chendi; Velagic, Anida; Qin, Cheng Xue; Li, Mandy; Leo, Chen Huei; Kemp-Harper, Barbara K.; Ritchie, Rebecca H.; Woodman, Owen L. (Frontiers in Pharmacology, 2021)
Introduction: Endothelial dysfunction is a major risk factor for several of the vascular complications of diabetes, including ischemic stroke. Nitroxyl (HNO), the one electron reduced and protonated form of nitric oxide (NO•), is resistant to scavenging by superoxide, but the role of HNO in diabetes mellitus associated endothelial dysfunction in the carotid artery remains unknown. Aim: To assess how diabetes affects the role of endogenous NO• and HNO in endothelium-dependent relaxation in rat isolated carotid arteries. Methods: Male Sprague Dawley rats were fed a high-fat-diet (HFD) for 2 weeks prior to administration of low dose streptozotocin (STZ; 35 mg/kg i. p./day) for 2 days. The HFD was continued for a further 12 weeks. Sham rats were fed standard chow and administered with citrate vehicle. After 14 weeks total, rats were anesthetized and carotid arteries collected to assess responses to the endothelium-dependent vasodilator, acetylcholine (ACh) by myography. The combination of calcium-activated potassium channel blockers, TRAM-34 (1 μmol/L) and apamin (1 μmol/L) was used to assess the contribution of endothelium-dependent hyperpolarization to relaxation. The corresponding contribution of NOS-derived nitrogen oxide species to relaxation was assessed using the combination of the NO• synthase inhibitor, L-NAME (200 μmol/L) and the soluble guanylate cyclase inhibitor ODQ (10 μmol/L). Lastly, L-cysteine (3 mmol/L), a selective HNO scavenger, and hydroxocobalamin (HXC; 100 μmol/L), a NO• scavenger, were used to distinguish between NO• and HNO-mediated relaxation. Results: At study end, diabetic rats exhibited significantly retarded body weight gain and elevated blood glucose levels compared to sham rats. The sensitivity and the maximal relaxation response to ACh was significantly impaired in carotid arteries from diabetic rats, indicating endothelial dysfunction. The vasorelaxation evoked by ACh was abolished by L-NAME plus ODQ, but not affected by the apamin plus TRAM-34 combination, indicating that NOS-derived nitrogen oxide species are the predominant endothelium-derived vasodilators in sham and diabetic rat carotid arteries. The maximum relaxation to ACh was significantly decreased by L-cysteine in both sham and diabetic rats, whereas HXC attenuated ACh-induced relaxation only in sham rats, suggesting that diabetes impaired the contribution of NO•, whereas HNO-mediated vasorelaxation remained intact. Conclusion: Both NO• and HNO contribute to endothelium-dependent relaxation in carotid arteries. In diabetes, NO•-mediated relaxation is impaired, whereas HNO-mediated relaxation was preserved. The potential for preserved HNO activity under pathological conditions that are associated with oxidative stress indicates that HNO donors may represent a viable therapeutic approach to the treatment of vascular dysfunction.